2014
DOI: 10.1002/jctb.4573
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial separation and characterization of Al–PE composites during delamination of post‐consumer Tetra Pak materials

Abstract: BACKGROUND: In order to understand Al-PE composite delamination during the separation process, interfacial separation and characterization of Al-PE composites during delamination were analyzed. The aim was to enrich the present theoretical analysis of Al-PE separation and to provideg new ideas for the recycling and reuse of post-consumer Tetra Paks. RESULTS: The composites delaminated into three layers, but the times for delamination of the two plastic layers were different. After separation, some plastics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Zhang et al [25] suggested that the delamination mechanism is the interfacial adhesive failure between the PE and the aluminium foil.…”
Section: Delaminationmentioning
confidence: 99%
“…Zhang et al [25] suggested that the delamination mechanism is the interfacial adhesive failure between the PE and the aluminium foil.…”
Section: Delaminationmentioning
confidence: 99%
“…Delamination occurred due to the swelling of PE and although some material loss was observed, it was lower than that obtained with separation using organic acids. A blend of benzene-ethanol-water (30:20:50 volume ratio) for 5 min at 60 • C was used to separate PolyAl layers; the bright spots of irregular particles with scattered distribution detected by SEM on the surfaces of the PE and Al were Al, O and C [83].…”
Section: Chemicalmentioning
confidence: 99%
“…16 These mechanical methods consume a high amount of energy and produce low-quality recyclates. On the other hand, in the chemical recycling process, various chemicals such as benzene−alcohol−water mixture 13 N,N-dimethylcyclohexylamine, 17 methanoic acid, 18 etc. have been used to recycle the metal−polymer composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…The separation of metal–plastic composite materials has been carried out by many researchers through mechanical and chemical processes. The mechanical recycling process generally proceeds through the size reduction of composite materials by shredding, cutting, or crushing . These mechanical methods consume a high amount of energy and produce low-quality recyclates.…”
Section: Introductionmentioning
confidence: 99%